85.0k views
4 votes
Given f(x) = 3x ^ 2 - 2x + 1 and g(x) = 2sqrt(x) + 4 determine the value of 2g * (4) - 3f * (- 1) .

Given f(x) = 3x ^ 2 - 2x + 1 and g(x) = 2sqrt(x) + 4 determine the value of 2g * (4) - 3f-example-1
User Kalmiya
by
5.9k points

1 Answer

3 votes

ANSWER:


2\cdot g(4)-3\cdot f(-1)=1

Explanation:

We have the following functions:


\begin{gathered} f\mleft(x\mright)=3x^2-2x \\ g\mleft(x\mright)=2√(x)+4 \end{gathered}

We calculate in each case the part corresponding to each function and then perform the subtraction:


\begin{gathered} 2\cdot g(4)=2\cdot(2\sqrt[]{4}+4)=2\cdot(2\cdot2+4)=2\cdot8=16 \\ 3\cdot f(-1)=3\cdot(3\cdot(-1)^2-2\cdot(-1))=3\cdot(3\cdot1+2)=3\cdot5=15 \\ \text{ Therefore:} \\ 2\cdot g(4)-3\cdot f(-1)=16-15=1 \end{gathered}

User Ppwater
by
6.4k points